Does dopamine deficiency affect sex-dependent prognosis in Parkinson's disease?. (September 2022) - Jeong, Seong Ho; Lee, Hye Sun; Lee, Phil Hyu; Sohn, Young H.; Chung, Seok Jong
Abstract: Introduction: A bundle of evidence indicates that biological sex is an important factor for clinical phenotypes as well as prognosis in Parkinson's disease (PD). We investigated the effect of nigrostriatal dopaminergic degeneration on longitudinal outcomes according to sex in patients with PD. Methods: We recruited 571 consecutive drug-naïve PD patients (279 men and 292 women) who were followed up for ≥2 years after their first visit to the clinic with baseline dopamine transporter (DAT) imaging. A Cox proportional hazard model was used to compare the risk of developing levodopa-induced dyskinesia (LID), wearing-off, freezing of gait (FOG), or PD dementia (PDD) between male and female PD patients. A mediation analysis was used to determine the relationship between biological sex, striatal dopamine deficiency, and longitudinal outcomes. Results: Female PD patients exhibited less severely decreased DAT availability in all striatal subregions than male PD patients. The future development of wearing-off and FOG did not differ according to sex. LID developed more frequently in female PD patients than in male PD patients, while the risk of PDD conversion was higher in male PD patients than in female PD patients. In the mediation analyses, the direct effect of biological sex on the development of LID or PDD was major, while the mediating effect through the striatal DAT availability was minimal. Conclusion: Differences in longitudinal outcomes according to biological sex may be ascribed to a non-dopaminergic basis. This study suggests that therapeutic strategies targeting the extra-nigrostriatal pathway should be considered in future trials. Highlights: Women with Parkinson's disease (PD) had relatively preserved nigrostriatal dopaminergic neuron at PD diagnosis compared to men. Women had a higher risk of levodopa-induced dyskinesia occurrence, while dementia conversion occurred more frequently in men. Sex-specific differences in longitudinal outcomes in patients with PD may be ascribed to a non-dopaminergic mechanism.